Inhibitory effect and mechanism of action of Carvacrol as a promising natural food preservative against Fusarium acuminatum causing postharvest rot of garlic scapes (Allium sativum L) - Li, Pei; Liu, Jing; Zhang, Liqun; Wu, Wenqing; He, Can; Tan, Boxi; Tang, Shijing; Yu, Lu (Frontiers in Microbiology, 2025)
During prolonged storage of garlic scapes (Allium sativum L.), the proliferation of microorganisms, particularly fungi, frequently causes postharvest rot, leading to moss-covered stem spots, tissue softening, depression, and even structural breakage. Carvacrol, a promising natural food preservative, exhibits various biological activities against different microorganisms. To investigate the inhibitory effects and mechanism of action of carvacrol against specific pathogens responsible for postharvest rot in garlic scapes, in this study, a specific pathogenic fungal strain responsible for postharvest rot in garlic scapes, designated as strain F, was initially isolated from symptomatic garlic scapes and identified as Fusarium acuminatum through a combination of morphological, physiological, and molecular biological analyses. Meanwhile, our findings revealed that carvacrol can significantly delay the onset of postharvest rot symptoms in garlic scapes and exhibit potent in vito inhibitory activity against Fusarium acuminatum, with a median effective concentration (EC50) of 36.17 μg/L. In addition, scanning electron microscope (SEM) observations indicated that carvacrol could induce irreversible alterations in the morphology and structure of the hyphae, leading to deformation and rupture. Furthermore, the combined transcriptome and proteome analysis results indicated that carvacrol primarily affects the steroid biosynthesis and MAPK signaling pathway cell signaling pathways in Fusarium acuminatum to interference compromises the integrity and stability of the cell membrane, consequently suppressing the growth and proliferation of Fusarium acuminatum.